Organização do trabalho e gestão de competências: uma análise do papel do regente coral - Amato Neto, João; Fucci Amato, Rita de Cássia (Revista Gestão da Produção Operações e Sistemas, 2007)
The main purpose of this paper is to analyze the choir conduction practice, from the concepts of work organizationand competence management. This way, such aspects are presented and discussed from a bibliographicalreview of the studied themes, relating the literature to the choir conduction practice. This paper, therefore,aims at providing subsidies to the performance of conductors and to the improvement in the understandingand development of the direction and organization activities regarding vocal groups. It is concluded, from thiscurrent investigation, that the understanding and the application of all these concepts can cause a pronouncedimprovement in the quality of the activities developed by the choir groups.Keywords: Work organization; Competence management; Leadership; Choir conduction.